Does tolerance matter? The spatial distribution of creative industries across cities in Indonesia - Brata, Aloysius Gunadi; Ambarwati, Diah Kartika; Lobo, Lorensius Toto; Patnasari, Yenny; Sukamto, Andreas (Quaestiones Geographicae, 2023)
The creative sector is one of the most rapidly growing sectors of the global economy. This sector can also play an important role in providing economic benefits for developing countries. Promoting the creative economy needs a better understanding of the underlying factors that account for its spatial distribution. One of the most important factors that may influence the development of creative industries is tolerance. This paper focuses on the spatial distribution of the creative economy across cities in Indonesia and examines its relationship with tolerance. The main data sources of this paper are the unique data produced by the Central Bureau of Statistics (Badan Pusat Statistik or BPS) and the Indonesian Agency for Creative Economy (Badan Ekonomi Kreatif or BEKRAF), in addition to the City Tolerance Index provided by the SETARA Institute. The study finds that the creative economy in Indonesia does not tend to have a high spatial concentration, indicating that cities in Indonesia have an opportunity to develop the creative economy. The analysis confirms that tolerance matters for the creation of the creative economy in Indonesia. Three components of the City Tolerance Index that influence the creative economy are the Mid-Term Regional Development Plan, discriminatory regional rules and incidents of abuses against the freedom of religion or belief. The size of the population, the Human Development Index, and the status of a city as the provincial capital play a significant role in explaining the distribution of creative economies across the cities in Indonesia.